United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper focuses on the housing and business cycles in the United Kingdom. The UK housing cycle is highly volatile as a result of tight housing supply constraints and fluctuations in credit conditions. Housing supply-side constraints can be alleviated through changes to the planning system and tax reforms. The new National Planning Policy Framework introduced by the government is creating the incentives for local councils to increase available land for construction. There are early signs that this change in the planning system is contributing to the recovery in housing construction. Targeted macroprudential policies could address financial stability risks stemming from the housing market. Although mortgage credit as a share of gross domestic product has been declining in the current housing recovery, there are signs that there is a build-up of financial risks: loan-to-income ratios are increasing in London and among first time buyers.